Plato’s Unwritten Doctrine - Krämer, Hans Joachim (Peitho. Examina Antiqua, 2015)
With the late Author’s (†24.04.2015) kind permission, the present text is published here in a somewhat abbreviated and modified translation that has been given appropriate subheadings and supplemented with an extensive bibliography. Its German original from 1996 has been translated into French (1998) and English (2012). The purpose of the present translation is to make the Polish reader acquainted with the important and innovative account of Plato’s philosophy that has been put forward by the Tübingen School whose one of the most prominent co-founders was Hans Joachim Krämer. While this text is devoted to Plato’s critique of writing, it also presents Plato’s agrapha dogmata as an important supplement to the written dialogues. A fuller overview of the major assumptions of this new interpretation is to be found in the recently published Gesammelte Ansätze zu Platon (2014).